True and Fair View of Key Performance Indicators in Evaluating Companies’ Compliance with the EU Green Taxonomy Regulation - Wanda Skoczylas; Przemysław Mućko; Gabriela Kintop (Nauki o Finansach)
Aim: Identify the problems and challenges faced by accounting in the process of legitimising organizations with financial mandatory key performance indicators that are designed to measure the share of the company’s environmentally sustainable activities.